IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL SEKOLAH - Anggriati Ledu Ngaba (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2017)
The aim of research is to analyze the implementation of the program of school operational assistance (BOS) on one Christian Primary School, West Sumba at the stage of preparation and implementation. The research method is descriptive with case studies. The technique of collecting data using interviews and document study. The analysis showed of BOS program implementation at the stage of preparation has been good, but the Decree of BOS management team is not published. The implementation stage is already very good but slow disbursement of funds from the government, transparency is good enough that involve committees and parents, accountability is good that is planning the use of funds in accordance with the format specified, the school also orderly administration accountability report, but not announced. DOI: https://doi.org/10.17977/um025v1i32017p254